1989
DOI: 10.1152/jappl.1989.67.5.1807
|View full text |Cite
|
Sign up to set email alerts
|

Muscle morphological and biochemical adaptations to training in obese Zucker rats

Abstract: The purposes of the present study were to characterize the histochemical and enzymatic profiles of various hindlimb skeletal muscles, as well as to determine maximal O2 consumption (VO2max) and respiratory exchange ratios (R) during steady-state exercise in the obese Zucker rat. The changes that occurred in these parameters in response to a 6-wk training program were then assessed. Obese rats were randomly assigned to a sedentary or training group. Lean littermates served as a second control. Training consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 0 publications
3
25
1
Order By: Relevance
“…Moreover, a recent study has shown increases in several mitochondrial enzymes after 28 days of AICAR treatment (28). These and similar effects are well known as adaptive phenomena found in chronically exercising muscles (2,13,14,29) and support the idea that repetitive AMPK stimulation could be involved in mediating these long-term adaptive changes. However, the possible effect of long-term AICAR administration on insulin-stimulated glucose uptake is unsettled.…”
Section: Es Buhl and Associatessupporting
confidence: 83%
“…Moreover, a recent study has shown increases in several mitochondrial enzymes after 28 days of AICAR treatment (28). These and similar effects are well known as adaptive phenomena found in chronically exercising muscles (2,13,14,29) and support the idea that repetitive AMPK stimulation could be involved in mediating these long-term adaptive changes. However, the possible effect of long-term AICAR administration on insulin-stimulated glucose uptake is unsettled.…”
Section: Es Buhl and Associatessupporting
confidence: 83%
“…34 ; r 2 ϭ 0.45, P Ͻ 0.05) and white (y ϭ 10.5x Ϫ0. 24 ; r 2 ϭ 0.34, P Ͻ 0.05) gastrocnemius muscles as well as total preperfusion triglyceride concentration (y ϭ 13.0x Ϫ0.36 ; r 2 ϭ 0.51, P Ͻ 0.05) (Fig. 4B) were exponential and found to be significant.…”
Section: Diabetes Vol 50 June 2001mentioning
confidence: 85%
“…The arterial-and venousspecific activities for palmitate did not vary over time and were not significantly different between the lean (52.9 Ϯ 6.8 and 50.1 Ϯ 6.1 Ci/mmol, respectively, P Ͼ 0.05) and obese (50.3 Ϯ 2.8 and 44.9 Ϯ 2.4 Ci/mmol, respectively, P Ͼ 0.05) rats. Total muscle triglyceride was calculated by estimating the contributions of red and white muscles to the perfused muscle mass (24). Statistical evaluation of the data was done using analysis of variance with Newman-Keul's test for post hoc multiple comparisons, when appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…The xanthine oxidase activity in muscle homogenates from obese Zucker rats tended to be reduced. This may be a reflection of a lower capillary density in the obese rats (32), although there is no consensus on this issue (33).…”
Section: Discussionmentioning
confidence: 99%